2018
DOI: 10.1186/s13071-018-3167-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluralaner plus moxidectin (Bravecto® Plus spot-on solution for cats) against Otodectes cynotis infestations in cats

Abstract: BackgroundThe efficacy of the fixed combination of fluralaner plus moxidectin for the treatment of Otodectes cynotis infestations was evaluated in cats after topical application.MethodsSixteen cats experimentally infested with O. cynotis were allocated randomly to two groups of 8 cats each. One group was treated topically with the fixed combination of fluralaner plus moxidectin at the minimum dose rate of 40 mg fluralaner and 2 mg moxidectin/kg body weight. The other group was treated with physiological saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
2
13
0
6
Order By: Relevance
“…Earlier studies had shown high activity of topical fluralaner against fleas for 12 weeks in naturally and experimentally infested cats [19, 20]. Furthermore, the efficacy of fluralaner against otodectic mites was previously reported in experimentally infested cats [1, 15]. In our present study, improvements in pruritus and otic clinical signs were observed after fluralaner treatment, and persisted up to Day 84.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Earlier studies had shown high activity of topical fluralaner against fleas for 12 weeks in naturally and experimentally infested cats [19, 20]. Furthermore, the efficacy of fluralaner against otodectic mites was previously reported in experimentally infested cats [1, 15]. In our present study, improvements in pruritus and otic clinical signs were observed after fluralaner treatment, and persisted up to Day 84.…”
Section: Discussionsupporting
confidence: 82%
“…Cats can be infested with several ectoparasite species, particularly Ctenocephalides felis and Otodectes cynotis that are responsible for dermatitis and ear infestation respectively [1, 2]. There are also some zoonotic pathogens such as Rickettsia felis and Bartonella felis , which can be transmitted by cat fleas [3].…”
Section: Introductionmentioning
confidence: 99%
“…Afoxolaner (no product available labeled for use in cats), selamectin plus sarolaner (Revolution Plus; Zoetis), fluralaner (Bravecto; Merck) and fluralaner plus moxidectin (Bravecto Plus; Merck) resolved O cynotis infestations in cats after a single application. [24][25][26][27]…”
Section: Otodectes Cynotismentioning
confidence: 99%
“…Afoxolaner efficacy has been demonstrated against Sarcoptes, Demodex and Otodectes infestations in dogs [ 6 , 7 , 9 , 14 , 16 ]. In cats, fluralaner, another isoxazoline compound was demonstrated efficacious against O. cynotis infestations in cats alone or in combination with moxidectin [ 28 ], as well as sarolaner, alone or in combination with selamectin [ 1 , 26 ]. Off-label use of oral afoxolaner, a dog-only product (Nexgard ® ), has been found to be efficacious against O. cynotis infestations in cats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%